Impacts of River Groove Propagation on Irrigation Infrastructural Failures - Kuntjoro Kuntjoro; Choirul Anwar; Didik Harijanto (Institut Teknologi Sepuluh Nopember, 2014)
Water supply of irrigation intakes are generally from the river. The system considers the lowest water level of the river on its mechanism. River groove propagation is a development of erosion at some parts and at the same time a development of sedimentation at the other parts of the river bed. This phenomenon is identified as an indication that cause the flood which might endangers the surrounding infrastructures. Analysis by KUN-QARSHOV method on Brantas river groove propagation in Mojokerto areas is acquired. Most progressive vertical meander shifting is at cross section KB63. The shift isas deep as 0.38 metres per year. The second progressive vertical meander shifting is at cross section KB64. The shift is as deep as 0.27 metres per year. The most progressive horizontal meander shifting is at cross section KB64. The horizontal shift moves toward the right cliff at 0.17 metres per year. The second progressive horizontal meander shifting occurs at cross section KB63. The horizontal shift moves toward the right cliff at 0.14 metres per year. The groove propagation could be more dangerous if there is a combination between vertical and horizontal shifts at the same time that might cause severe cliff slides. The failure of the irrigation sytem at Brantas River in Mojokerto areas was due to the water level of the river below the irrigation intake level. Among others are the intakes at Keboan, Ngareskidul, and Gedeg irrigation areas. Another is due to the erosion of river bed at the syphon of Watudakon irrigation area.